Interactions between Water Evaporation and Surface Cracking in NaCl-Induced Homogeneous Silt Loam and Sand. Issue 15 (22nd August 2022) - Xing, Xuguang; Jing, Xiaoyuan; Zhao, Fengyue; Wang, Weihua
ABSTRACT: The processes of soil cracking with water loss in saline soils are still not well understood. It is of great significances to further understand the mechanism of desiccation cracking in saline-alkali soil and provide guidance for engineering practice in saline-alkali area. Silt loam and sand samples were saturated with NaCl solutions (5, 50, and 100 g/L) and undergone the evaporation tests, during which the water loss and surface cracking parameters were obtained. Results showed that evaporation and crack development influenced each other. The evaporation rate for both sand and silt loam samples saturated by NaCl solution was lower than the reference samples, and decreased as the concentration of NaCl solution increased. In addition, the water content for both two types of samples first rapidly decreased and then entered a stable state during evaporation; however, silt loam soil moisture experienced a "second decline" when surface crack developed rapidly. Compared to the reference sample, NaCl solution inhibited crack development in silt loam, which in turn impeded water evaporation; however, no surface cracks were observed in sand samples. Furthermore, crack area and crack length decreased as the concentration of NaCl solution increased, and higher NaCl concentration resulted in an earlier abrupt increase in crack number followed by a stable state. The present findings reveal that the interaction between water evaporation and surface cracking is shown by soluble NaCl, including the chemical effects on soil particles from free Na + and the physical effects on soil pores from precipitated NaCl crystals during water loss.